PLD.11 Characteristics of successful vaginal breech deliveries: A retrospective observational study in a tertiary centre. (9th June 2014) - Hartigan, L; Hehir, MP; Mone, F; Mahony, R
Abstract : Objectives: Firstly, to assess the incidence of vaginal breech deliveries within a tertiary obstetric unit. Secondly to determine obstetric characteristics and thirdly, the maternal and fetal outcomes of this population over an 11-year period following the publication of the 'Term breech trial'. Methods: A retrospective observational study of prospectively gathered data on vaginal breech deliveries over an 11-year period from 2001 to 2011 at a large tertiary referral obstetric centre. The delivery of still-born infants and those with lethal congenital anomalies were excluded. Data analysis was performed through Microsoft Excel. Results: Our study included 2, 346 term breech deliveries over the study period. The rate of vaginal breech deliveries was 5% (119/2346). 76.5% of cases occurred in multiparous patients (91/119) p < 0.05 and in 38.7% of cases delivery occurred beyond 40 completed weeks gestation (46/119) and was associated with rapid labour progression (39.5% <60 min (47/119)). The patient required an episiotomy for delivery in 52.1% of cases (62/119). Of infants delivered, 3.3% were macrosomic (4/119). 4.2% had an Apgar of <7 at 5 minutes (5/119) and cord pH level was <7.0 in 3.3% of cases (4/119). Conclusion: Vaginal breech deliveries are more likely to occur in multiparous women who have relatively short duration of labour. The maternal and fetal outcomes are overall reassuring.